Nasu-Hakola Syndrome: An Unusual Cause of Pathological Fractures - Jaykar R. Panchmatia; Natasha Jiwa; Neil Soneji; John Paul Murphy (Case Reports in Orthopedics, 2012)
Nasu-Hakola syndrome is a hereditary cause of pathological fractures. Uniquely, patients also develop neuropsychiatric symptoms and signs. The disease is ultimately fatal. We propose a management strategy for pathological fractures in sufferers based on the stage of the disease.